INTELLIGENT TRANSPORTATION SYSTEMS AND AGGRESSIVE DRIVERS - Krchova, Zuzana (Doprava a spoje, 2011)
In the first chapter, the aggressive drivers' behaviour is defined and is said how can be this behaviour expressed. In the second chapter, the characteristic of the intelligent transport systems and their ability to protect road users against the aggressive drivers is described and this is followed by use of ITS by fleet and risk management to recognize their risky drivers.